Expert System Detection of Disease Due to Bacteria Salmonella using Android-Based Forward Chaining Method - Mochammad Bisri Mustofa; Ika Ratna Indra Astutik (Universitas Muhammadiyah Sidoarjo, 2022)
Many diseases are caused by unhealthy food, one of which is Salmonella bacteria. Diseases from the Samonella bacteria can attack the digestive tract which includes the stomach, small intestine, and large intestine or colon. Some species of salmonella can cause infection through food. This includes Salmonella Typhi and Salmonella Shigella. Based on the problems above, there are still many people who do not know the symptoms of this bacterial disease and how to diagnose it with a high certainty value. With the aim of making an expert system application through each android phone by means of a diagnosis through the signs and symptoms. The researcher chose to use the forward chaining method. This method was chosen because this method is considered capable of providing a high level of certainty. The forward chaining method is one of the decision-making strategies starting from facts to conclusions or final conclusions. The result of this research is to create an android-based expert system application that can diagnose diseases caused by salmonella bacteria based on existing symptoms using the forward chaining method. This expert system has the benefit of providing good education to the public regarding diseases caused by salmonella bacteria.